Validation of molecular markers for stem rust resistance and identification of suitable wheat germplasm targeting Eastern Gangetic plains of India - Yadav, P.S.; Mishra, V.K.; Arun, B.; Chand, R.; Joshi, A.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Five molecular markers were used to identify stem rust resistance genes, namely, Sr2, Sr22, Sr25/Lr19, Sr50 and SrWeb in eight diverse wheat lines from CIMMYT, Mexico and India that included three popular cultivars of north eastern Gangetic plains of India. One of the CIMMYT line, PMWBIR4 carried all the above mentioned five Sr genes, while other lines showed different combinations. The identified wheat genotypes may be useful in stem rust resistance breeding. Validation of linked markers for rust resistance suggested that the markers can be deployed in marker assisted molecular breeding program.